Pentingnya Inovasi Pembelajaran Puisi dengan Menggunakan Ragam Media Pada Tingkat Sekolah Dasar - Julianto, Indra Rasyid (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is intended as a reference to understand that teachers have a variety of learning media that can be maximally utilised in learning to write poetry in primary schools. This shows that digitalisation in education requires teachers to continue to innovate in the learning process at the primary school level. With the right use of media, poetry writing skills become easier to understand. Media helps students interpret the meaning contained in various types of media used. With the help of media, students can produce poems that are arranged systematically and structured. The role of the teacher who delivers the material is also very influential in the smooth running of learning. The use of media in learning poetry creates a new atmosphere for students, so they are not only focused on books or methods that are difficult to understand. This research also uses a qualitative descriptive method with literature studies from various articles that support the research process